Zaposleni v digitalni dobi - Podbregar, Iztok (2020)
Employees in the Digital Age. The scientific monograph contains a series of chapters which in its baseline generating an employee, i.e. an individual who, in anticipation of new solutions, technologies and goals, contributes to the realization of the organization and its objectives. The first section links the context of the development of technology and human resource management. The first chapter is followed by a presentation of the employment field in the digital age, characterized by accelerated growth in technology development on the one hand, and demographic change and globalization on the other. The next section presents the role of human resource management in terms of integration and dissemination of various aspects of the ecosystem in which employees live and work. Followed by a section that focuses puts into young people. It looks at how young people are climbing from formal education systems to the four walls of organizations that can represent security on the one hand, and the possibility of rising even higher on the other. This is followed by a presentation of forms of education and the impact of information and communication technology on education. The monograph concludes with a contribution that links the building blocks of organizational culture in various segments of society.
Keywords: information technology; Human resource management; employment process; CV card; digital age; Employment; Nature of work; Non-standard forms of employment; ecosystem; digitization; communication; crisis manager; opportunities for youth; crisis; education; information and communication technology; digital transformation; organizational culture; GLOBE; sports organizations; tourism associations; ICT; HRM